Frequency response services designed for energy storage. (1st October 2017) - Greenwood, D.M.; Lim, K.Y.; Patsios, C.; Lyons, P.F.; Lim, Y.S.; Taylor, P.C.
Highlights: The need for improved frequency response in future power systems is identified. An investigation into how energy storage can fulfil this need is presented. New experimental methods have been developed, using power hardware in the loop. Analysis of high-resolution frequency data from the British electricity system. Case study analysis of a new frequency response service designed for energy storage. Abstract: Energy Storage Systems (ESS) are expected to play a significant role in regulating the frequency of future electric power systems. Increased penetration of renewable generation, and reduction in the inertia provided by large synchronous generators, are likely to increase the severity and regularity of frequency events in synchronous AC power systems. By supplying or absorbing power in response to deviations from the nominal frequency and imbalances between supply and demand, the rapid response of ESS will provide a form of stability which cannot be matched by conventional network assets. However, the increased complexity of ESS operational requirements and design specifications introduces challenges when it comes to the realisation of their full potential through existing frequency response service markets: new service markets will need to be designed to take advantage of the capabilities of ESS. This paper provides new methods to analyse and assessing the performance of ESS within existing service frameworks, using real-time network simulation and power hardware in the loop. These methods can be used to introduce improvements in existing services and potentially create new ones. Novel statistical techniques have been devised to quantify the design and operational requirements of ESS providing frequency regulation services. These new techniques are demonstrated via an illustrative service design and high-resolution frequency data from the Great Britain transmission system.